(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Environmental problems have become serious in many parts of the country, and hence cannot be ignored. The main environmental problems in India relate to air and water pollution particularly in metropolitan cities and industrial zones, degradation of common property resources which affect the poor adversely as they depends on them for their livelihood, threat to biodiversity and inadequate system of solid waste disposal and sanitation with consequent adverse impact on health, infant mortality and birth rate. There are many environmental issues in India. According to data collection and environment assessment studies of World Bank experts